If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) = -5x Reorder the terms: 2(4 + x) = -5x (4 * 2 + x * 2) = -5x (8 + 2x) = -5x Solving 8 + 2x = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 8 + 2x + 5x = -5x + 5x Combine like terms: 2x + 5x = 7x 8 + 7x = -5x + 5x Combine like terms: -5x + 5x = 0 8 + 7x = 0 Add '-8' to each side of the equation. 8 + -8 + 7x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 7x = 0 + -8 7x = 0 + -8 Combine like terms: 0 + -8 = -8 7x = -8 Divide each side by '7'. x = -1.142857143 Simplifying x = -1.142857143
| 2x+4=-5x+1 | | 49n^2-81=0 | | 100=(x+2)+(x/2) | | -28=92+10x | | 100=x+2+x/2 | | 2(2w+12)=68 | | 4x-2(-1x-11)=64 | | 25a^2-80a+64=0 | | Z^2+8=4 | | a+(37+a)+(2a-40)=433 | | s-32=-29 | | 2x+8=352 | | (x)(x+1)(x+2)=36 | | 8x-(5x+4)=7+(2x-3) | | -5x+4(-3+3)=-192 | | x^2*y-3*x*y=0 | | 5(2a+4)=6a-4 | | 1.2m=.6 | | (x^2-5x-3)(x^2-5x-5)=3 | | -x+6x-9=0 | | 2y=-10x+4 | | -7=9x+16-10 | | 2(x+p)=3(6p-x) | | 9k-3k=30 | | 3y+4=y+18 | | -44-1x=28-4x | | x-7.1=-6.2 | | -(3y+1)-(-2y-7)=2 | | 96-2x=43x+16 | | 7(7x-3)+10x= | | 2x+80=158 | | 5p-3=32 |